The trophic dynamics of the broadnose sevengill shark (Notorynchus cepedianus) in False Bay, South Africa, using multiple tissue stable isotope analysis - De Necker, Leigh (Department of Biological Sciences, 2017)
Despite their important ecological role, there is limited quantitative information on the trophic ecology of large, apex predator sharks. This is largely a consequence of their occupying naturally low population densities, being highly mobile and elusive and ranging over large distances. Stable isotopes provide a low cost, non-lethal method for investigating the short and long-term diet of a predator, which when combined with prey data can be used to understand the trophic interactions and the potential regulatory effects they may have on the structure and function of marine ecosystems. In this study, I used non-lethal stable isotope analysis to investigate the trophic dynamics of sevengill sharks, Notorynchus cepedianus, within False Bay, South Africa. A total of 39 muscle biopsies (33 female, six male), and 28 blood plasma samples (25 female, three male) were collected from sevengill sharks. These were analysed together with 161 prey samples from 32 different species, including cephalopods, crustaceans, teleosts, chondrichthyans and marine mammals. In addition, seven white shark, Carcharodon carcharias, muscle samples were collected from False Bay and analysed for comparison with those of sevengills. Sevengills in False Bay had the highest δ15N values of all species sampled in this study (including white sharks) and appear to feed predominantly on a variety of coastal prey species from various functional groups. A stable isotope mixing model revealed that inshore chondrichthyans were their most important prey, with Cape fur seals and inshore teleost species also being important prey groups. There was no apparent seasonal shift in the diet of sevengills, despite clear seasonal aggregation in coastal kelp forests during the summer months. δ15N decreased significantly with sevengill size, with immature females having higher δ15N values than mature females, while δ13C increased with sevengill size. These trends are hypothesised to be linked to dietary shifts associated with the relative use of different habitat types when individuals become sexually mature. There is a need to combine stable isotope data with movement patterns and habitat use to better understand the relationship between isotope ratios and habitat use. Ongoing research on sevengill and white shark movement patterns in False Bay, together with the results presented in this study, will provide important information on the trophic and ecological role that two top predatory sharks play in False Bay. Keywords: Notorynchus cepedianus, sevengill shark, stable isotopes, trophic ecology